Factibilidad para la Implementación de una Empresa Productora y Comercializadora de un Saborizante de Haba en la Ciudad de Catacocha Cantón Paltas Provincia de Loja - Villano Diaz, Glenda Magaly (2017)
The present work aims to present a proposal for the implementation of a company producing and marketing bean flavor in the city of Catacocha, Canton Paltas. Within the objectives was proposed to carry out the market study to know the demand, supply and demand unsatisfied, also the technical study was carried out to determine the location of the project where the macro and micro location is shifted, a proposal was found Administrative-functional of the company to be implemented; Through the collection of data with the survey technique, information was obtained for the results of this research. The information obtained through the applied survey has been processed through a qualitative approach using its own descriptive and sustained techniques through the theoretical bases of study. The market study analyzed the demand and supply to determine the reception that the product has in the market. Resulting in an effective claim of 60,887 plaintiffs and an unsatisfied demand for year zero of 51,644 pounds. The technical study was then carried out which took into consideration the installed capacity of which determined that the company is in the production capacity 96,360 pounds of flavorings and with capacity of 22,880 pounds of bean flavoring; In the same way the size and location, plant layout, project engineering, organic - functional structure, constitution, organization and function manuals, the same as the fundamentals of son for the implementation of a good organization. In the financial study it was determined that the project obtained an investment of $ 18,642.54 and was financed with a contribution of 100% of the total investment. The financial evaluation indicators showed positive and encouraging results to ensure a good profitability of the project where the Net Real Value (NPV) is calculated, generate a positive result for the company with an amount of $ 88,757.68 which means that the project The Internal Rate of Return (IRR), 130.67%, Cost Benefit Ratio (RBC), yields a result of 26 cents, the Capital Recovery Period (PRC), 9 Months and 10 days. The sensitivity analysis supports an increase in costs of 4.70% and a decrease in revenues of up to 4.50%, obtaining a sensitivity of 0.99. It was later concluded that there is a feasibility of creating the company producing and selling a bean flavor in the city of Catacocha: since according to the results obtained it was determined that the project is feasible. Finally, the conclusions, recommendations, bibliography and annexes were found.